NUTRITIONAL AND HEALTH STATUS OF LODHA TRIBAL WOMEN OF MAYURBHANJ DISTRICT IN COMPARISION TO THEIR MALE COUNTERPARTS - JHUNILATA BHUYAN; SASMITA BEHERA (The Journal of Research ANGRAU, 2022)
Lodha is a primitive tribe living in a dense forest area of West Bengal, Odisha, and Jharkhand. This study was conducted to determine the nutritional status of both male and female Lodha tribes. A total of 400 Lodha tribal people including 200 males along with 200 tribal females were selected randomly in the age range for all groups was 18-45 years and belonged to the non-pregnant and non-lactating category. A total of 400 subjects were randomly selected from 10 villages of Morada, Baripada, Shamakhunta from the Suliapada block of Mayurbhanj district. The prevalence of Chronic Energy Deficiency (CED) among female Lodha tribe (82.5%) was significantly higher ( =15.635, p= 0.0015) than their male counterparts (57%). This study also reported that the male Lodha tribal were more affected by the overweight and obese category of Chronic Energy Deficiency CED. These also warned the tribal families about the arrival of the burden of overweight and obesity, the opposite side of malnourishment. All the physiological parameters like pulse rate, systolic pressure, and a diastolic pressure of female tribal had lower than the male tribal. However, the difference between them was not significant ( =0.2002, p=0.1014). Similarly, this study also stated there was no significant difference ( =2.441, p=0.4887) of morbidity patterns like skin infection, intestinal infections, respiratory infections, and vitamin deficiencies of male and female Lodha tribal people.